2017
DOI: 10.1080/00016489.2017.1284343
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF expression as a potential biomarker of acquired middle ear cholesteatoma

Abstract: On average, compared with normal postauricular skin, expression of HB-EGF mRNA in the cholesteatoma epithelium was significantly elevated 2.41-fold by RT-qPCR, and HB-EGF protein significantly upregulated 2.32-fold by western blot. Positive HB-EGF immunostaining observed in the basal and suprabasal layers of cholesteatoma epithelium was significantly stronger than in normal postauricular skin. Meanwhile, an obviously positive correlation between HB-EGF protein expression and bone resorption degree was discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Although many studies have investigated the mechanisms of cholesteatoma formation, its pathogenesis remains unclear [1]. Many molecules and proteins have been investigated [13][14][15][16]. Studies on cholesteatoma tissue have shown that epidermal growth factor receptor (EGFR) disorder plays a role in the development of cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have investigated the mechanisms of cholesteatoma formation, its pathogenesis remains unclear [1]. Many molecules and proteins have been investigated [13][14][15][16]. Studies on cholesteatoma tissue have shown that epidermal growth factor receptor (EGFR) disorder plays a role in the development of cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesteatoma is known as a severe chronic middle ear disease that occurs in the middle ear, eventually causing adverse complications with rapid growth and bone resorption [ 23 ]. It accounts for 0.5–1.8% of all brain tumors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade it has become obvious that there is not one gene suitable for use of normalisation for all tissue types [ 40 ]. In the field of middle ear research many different genes have been used, such as B2M [ 52 ], PPIA [ 9 ], ACTB [ 33 , 34 ], HPRT1 [ 35 ] and GAPDH [ 36 39 ]. Interestingly, all articles published to this date use only one gene for normalisation, even though it has been abundantly shown that this is not sufficient for reliable analysis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…QPCR has been used in several studies related to diseases of the middle ear. However, there seems to be little consensus as to which reference genes to use for normalisation, leading to the use of several different genes without proper establishment of which genes are appropriate [9,[31][32][33][34][35][36][37][38][39]. To be able to obtain reliable results the use of stably expressed reference genes for normalisation is essential [40].…”
Section: Introductionmentioning
confidence: 99%